Three Power Dance Drive Out Corona with Gendhing Sanghyang Kinan: An Apotropaic Dance Performed on the World Dance Day as Prayer to God Almighty - Sawitri Sawitri (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Dance is the result of human creativity expressed in the form of motion. The process aims to express oneself, ideas, and thoughts in a form of work that can be enjoyed by others. Three Power Dance Drive Out Corona is a dance inspired by the COVID-19 pandemic. The research data was obtained from journal and literature studies, as well as interviews. This article aims to reveal the purpose of this corona-themed dance. The method used is descriptive-qualitative using field data, data analysis, reduction and data grouping for primary and secondary data. Supporting data obtained from magazines, internet, newspapers can strengthen the validity of the data. Interviews were conducted with art observers, dance masters, and the public watching the performances even though they were virtual. This corona-themed dance using gendhing sanghyang kinan is purposed as an apotropaic dance so that the corona can end quickly and be away from the land of Java and Indonesia. The COVID-19 pandemic has a very huge impact on human life, not only Indonesia but also the world. A work of dance born during a pandemic is a form of concern and prayer to God Almighty for the blessing of health. The pandemic has lasted for almost two years and the exhaustion of the community has been felt but the 5M protocol must always be obeyed. This apotropaic dance is a hope for the end of the pandemic.